The Manipulation of Indonesia's Ethnic Chinese: The TWSC Interview with Ariel Heryanto - Center, Third World Studies (Kasarinlan: Philippine Journal of Third World Studies, 2007)
The fall of Suharto has been viewed as the Southeast Asian region's most astonishing event of late. The tension and destruction in Jakarta and other Indonesian cities and the former dictator's startling ouster sent the country of 200 million into a wave of shock and relief. The events certainly compounded the economic crisis that had plunged about 40 percent of the population into poverty. The dramatic process reduced to a sideshow the systematic gang raping of 162 women and girls, mostly ethnic Chinese, that accompanied the 1,200 deaths that occurred during the May 13-14 riots. Having designated blame on spontaneous eruptions of racism unleashed upon the Chinese minority, the rest of the country is only now grappling with the horror even as it braces for hardship in the days to come. It has become clear, however, that the so-called anti-Chinese riots were anything but spontaneous. They were in fact premeditated and organized acts of terrorism of a regime that was in its death throes. Last May 25, the Third World Studies Center asked Dr. Ariel Heryanto to shed light on these tumultuous events, Dr. Heryanto, a lecturer at the Southeast Asian Studies Programme ofthe National University of Singapore, has done several researches on student movement and middle class politics in Indonesia.